Flexible Viruses 2011
DOI: 10.1002/9781118135570.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Do Viral Proteins Possess Unique Features?

Abstract: Many proteins (or protein regions) are intrinsically disordered. They lack unique 3D structures in their native, functional states under physiological conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 193 publications
(184 reference statements)
0
8
0
Order By: Relevance
“…The proportions of predicted continuous disordered segments are shown as a function of the length of the disordered region. Data were taken from ref .…”
Section: Prevalence Of Intrinsic Disorder In Viral Proteins As Unveil...mentioning
confidence: 99%
“…The proportions of predicted continuous disordered segments are shown as a function of the length of the disordered region. Data were taken from ref .…”
Section: Prevalence Of Intrinsic Disorder In Viral Proteins As Unveil...mentioning
confidence: 99%
“…Indeed, the high content of intrinsic disorder predicted in viruses agrees with a recent study which showed that viral proteins were significantly enriched in polar residues and depleted in hydrophobic residues compared with that of archaea and bacteria, 109 which correlates with their disorderedness. 110 , 111 The high intrinsic disorder in viral proteins is supposedly linked to important functional implications, helping the viruses to highjack various pathways of the host cells and/or to accommodate to their hostile habitats. 110 , 111 The roles of IDPs/IDRs in certain viral proteins upon viral infections have been explored but are not yet completely understood, including membrane-binding protein λN of bacteriophage, horde virus protein TGBp1, influenza virus nonstructural protein 2, basic protein δAg of hepatitis B virus, and human adenovirus type 5.…”
Section: Intrinsically Disordered Proteins In Sars-cov-2 Proteome And...mentioning
confidence: 99%
“… 110 , 111 The high intrinsic disorder in viral proteins is supposedly linked to important functional implications, helping the viruses to highjack various pathways of the host cells and/or to accommodate to their hostile habitats. 110 , 111 The roles of IDPs/IDRs in certain viral proteins upon viral infections have been explored but are not yet completely understood, including membrane-binding protein λN of bacteriophage, horde virus protein TGBp1, influenza virus nonstructural protein 2, basic protein δAg of hepatitis B virus, and human adenovirus type 5. 1 …”
Section: Intrinsically Disordered Proteins In Sars-cov-2 Proteome And...mentioning
confidence: 99%
“…Also, a remarkable discovery that tryptophan conformation and absolute stereochemistry could be determined from the signs of the tryptophan W3 ROA bands was made from ROA data on filamentous bacteriophages [33], further insight into this assignment being provided by later DFT calculations [63]. The importance of intrinsic disorder in viral coat proteins is being increasingly recognized, especially to facilitate rapid changes at almost all stages of their life cycle, with many functions attributed to disordered regions [101]. In fact the strong positive ∼1316 cm −1 band in the ROA spectrum of STMV (Fig.…”
Section: Virusesmentioning
confidence: 99%